Torque Mode-Based Flywheel System For Small Satellite Attitude Control - Mehedi, Ibrahim Mustapa (2005)
One of the most important problems in satellite design is that of attitude control. An architecture of attitude control for small satellite using flywheel system is proposed. This flywheel system can combinedly perform both the energy and attitude control task that are the crucial area for all types of satellites. Combining the conventional energy and attitude control system is a feasible solution for small satellites to improve the space missions. In this combined energy and attitude control system (CEACS) a double rotating flywheel in the pitch axis is used to replace the conventional battery for energy storage as well as to control the attitude of an earth oriented satellite. Each flywheel is to be controlled in the torque mode. The energy and attitude inputs for the flywheels' control architecture are also in the torque mode. All related mathematical representations along with the relevant transfer functions are developed. The required numerical calculations are performed using at lab^^ for studying the system performances. The goals of this work are to determine the CEACS attitude performance in the torque mode with respect to the ideal and non-ideal test cases for chosen reference missions, i.e., Nanosatellite (10 kg), Microsatellite (50 kg) and Enhanced Microsatellite (100 kg). The test results concerning to the entire satellite test cases are satisfactory and the ideallnon-ideal CEACS attitude performances coincide with the reference mission requirements. The simulation results show that the torque mode CEACS is able to achieve a good pointing error for small satellites.